2007
DOI: 10.1002/hep.21633
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function does not worsen during pegylated interferon and ribavirin retreatment of chronic hepatitis C†‡

Abstract: Treatment of chronic hepatitis C with pegylated interferon (peginterferon) and ribavirin can cause or exacerbate depression but its effects on cognitive function are largely unknown. The aim of this study was to determine whether treatment with peginterferon and ribavirin adversely impacts cognitive function in patients with chronic hepatitis C. Prior nonresponders to interferon were retreated with peginterferon alfa-2a and ribavirin for 24 (n ‫؍‬ 177) or 48 weeks (n ‫؍‬ 57) in the Hepatitis C Antiviral Long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
5
35
1
Order By: Relevance
“…Among HCV-positive individuals, only one study found minor impairment, whereas four other studies found this domain intact in individuals with HCV infection [18,21,37•,41•]. Cordoba et al [21] found verbal fluency impairments among HCV-positive individuals with decompensated cirrhosis.…”
Section: Executive Functionmentioning
confidence: 95%
“…Among HCV-positive individuals, only one study found minor impairment, whereas four other studies found this domain intact in individuals with HCV infection [18,21,37•,41•]. Cordoba et al [21] found verbal fluency impairments among HCV-positive individuals with decompensated cirrhosis.…”
Section: Executive Functionmentioning
confidence: 95%
“…However, other studies have not demonstrated a difference in psychometric performance of cirrhotics with chronic hepatitis C compared to those without it [30,34] . In addition, a recent detailed study before and after interferon therapy in chronic hepatitis C cirrhotics failed to find an improvement or deterioration during and after therapy completion [35] . Diabetes mellitus is an important correlate of patients with cirrhosis, with the increasing importance of non-alcoholic steatohepatitis, and is also correlated with chronic hepatitis C in the general population [36] .…”
Section: Contribution Of Concomitant Diseases To Mhementioning
confidence: 99%
“…First, this study addresses major limitations of the previous longitudinal neurocognitive studies noted above. Few studies have taken into account naturally occurring change and practice effects on repeated neurocognitive test performance, which is a possible explanation of the diverging findings for past studies on both HCV/HIV co-infection (Giesen et al 2004; Ryan et al 2004; Clifford et al 2005; Hilsabeck and Castellon 2005; Hinkin et al 2008) and pegylated IFN/RBV treatment studies (Fried 2002; Hilsabeck and Hassanein 2005; Fontana et al 2007; Wobrock et al 2008; Fontana et al 2010; Group et al 2014; Huckans et al 2015). We controlled for practice effects by adopting the standard regression based approach, which utilized norms for change (McSweeny et al 1993; Hinton-Bayre 2010a; Maassen 2010; Hinton-Bayre 2010b; Cysique et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study did not assess whether neurocognitive decline sustained or improved upon treatment discontinuation. Past research (e.g., Fontana et al (2007; 2010)) leads us to assume upon the discontinuation of IFN/RBV treatment neurocognitive functioning would likely be improved. Lastly, the introduction of direct acting antiviral therapy for the treatment of Hepatitis C has dramatically transformed the treatment of HCV among both mono- and co-infected patients such that IFN is no longer used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation